Catasetum × guarayense (Orchidaceae: Catasetinae), first formally described and documented natural hybrid of the genus for Bolivia - Krahl, Amauri Herbert (2026)
Catasetum × guarayense is described and illustrated as the first natural hybrid of Catasetum reported from Bolivia. The material was collected in the municipality of El Puente, Guarayos province, Santa Cruz department, in the central eastern region of the country. In addition, data on its geographical distribution, habitat, and phenology are provided. The available evidence suggests that the hybrid results from the natural crossing between C. rooseveltianum and C. semicirculatum, species occurring within the limits of the Bolivian territory. As expected for any natural hybrid, compared to its probable parents, C. × guarayense presents a set of intermediate morphological characters, a point discussed in detail in this study. Besides, we propose an identification key to the Bolivian Catasetum species with symmetrical and parallel antennae.